Efficacy of corticosteroids for hand osteoarthritis - a systematic review and meta-analysis of randomized controlled trials - Mahnuma Mahfuz Estee; Flavia M. Cicuttini; Matthew J. Page; Anant D. Butala; Anita E. Wluka; Sultana Monira Hussain; Yuanyuan Wang (BMC Musculoskeletal Disorders, 2022)
Abstract Background There is some evidence that corticosteroids may have a beneficial effect in hand osteoarthritis. We examined the efficacy of corticosteroids on symptoms and structural outcomes in hand osteoarthritis. Methods Ovid MEDLINE, Embase and Cochrane Central Register of Controlled Trials were searched from inception to October 2021 for randomized controlled trials investigating the efficacy of corticosteroids in hand osteoarthritis. Two authors independently screened records, extracted data, and assessed risk of bias using the RoB 2 tool. Standardized mean difference (SMD) or mean difference (MD) was calculated, and random-effects meta-analyses were performed. Results Of 13 included trials, 3 examined oral corticosteroids and clinical outcomes in any hand joints, 9 examined intra-articular injection of corticosteroids and clinical outcomes at the first carpometacarpal joint and one in the interphalangeal joints. In meta-analysis, oral corticosteroids reduced pain (SMD -0.53, 95% CI -0.79 to -0.28) and improved stiffness (MD -5.03, 95% CI -9.91 to -0.15; Australian Canadian Osteoarthritis Hand Index stiffness subscale) and function (SMD -0.37, 95% CI -0.63 to -0.12) at 4-6 weeks. However, there was no significant persistent effect on pain and function at 3 months which was 6-8 weeks after study medication was stopped. There was no significant effect of intra-articular corticosteroids on pain or function at 4-6 weeks or over 3-12 months in first carpometacarpal osteoarthritis. Two trials evaluated joint structure at 4-6 weeks: one study showed oral corticosteroids reduced synovial thickening, neither showed an effect on synovitis. Conclusions There was low-certainty evidence for a medium effect of oral corticosteroids on pain relief and stiffness improvement and small-to-medium effect on functional improvement at 4-6 weeks, with no significant effect for intra-articular corticosteroids. Corticosteroids had no significant effect on any outcomes over longer term (3-12 months) off treatment. No trials examined the effect of corticosteroids on disease progression. The role of corticosteroids in hand osteoarthritis is limited.